A randomized, open-label clinical trial to evaluate immunogenicity and safety of an indigenously developed DTwP-Hib tetravalent combination vaccine (Easyfour®-TT) with Quadrovax® in Indian infants - Lalitendu Mohanty; Sunil Sharma; Beauty Behera; Sachin Panwar; Charu Paliwal; Anit Singh; Anu Gupta; Deepak Chandra Chilkoti (Taylor & Francis Group, 2017)
An open-label, randomized, multi-center trial was conducted to compare the immunogenicity and safety of an indigenously developed tetravalent DTwP-Hib vaccine, Easyfour®-TT with a commercially available vaccine, Quadrovax®. A total of 244 infants in good health, aged 6-10 weeks, were randomized in a 1:1 allocation to receive three doses of the test or comparator vaccine. Immunogenicity of the vaccines was determined by measuring the baseline and post-vaccination antibody response against the vaccine antigens; safety was evaluated in terms of local and systemic reactions (solicited and unsolicited) reported during the trial. Similar levels of seroprotection/seroresponse were achieved, 4 weeks after receiving 3 doses of Easyfour®-TT and Quadrovax®, and the antibody response of Easyfour®-TT was found non-inferior to Quadrovax®, against all four vaccine antigens. Both vaccines were well tolerated and had similar reactogenicity profiles, with a significantly lower occurrence of local (redness at injection site) and systemic reactions (irritability post-vaccination) with Easyfour®-TT vaccine as compared to Quadrovax® (p < 0.05). All adverse events resolved completely with no sequelae. All through the study, only one serious adverse event was observed that completely resolved upon treatment and was deemed unrelated to the vaccine administered. This study demonstrated that Easyfour®-TT vaccine was safe and immunogenic. Clinical trial registration number: CTRI/2014/12/005326 (registered with the Clinical Trial Registry of India (CTRI)).